2005
DOI: 10.1007/s00066-005-1338-2
|View full text |Cite
|
Sign up to set email alerts
|

Neck Lymph Node Metastases from an Unknown Primary Tumor

Abstract: With radical surgery followed by radiotherapy good survival rates in patients with neck metastases from a CUP can be obtained. Whether limited radiotherapy might be equal to extended irradiation and can reduce side effects, must be shown in ongoing clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0
7

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 39 publications
4
18
0
7
Order By: Relevance
“…The estimated OS after 5 years was 63%. Both values are at least in line with or even superior to other published data 911…”
Section: Discussionsupporting
confidence: 91%
“…The estimated OS after 5 years was 63%. Both values are at least in line with or even superior to other published data 911…”
Section: Discussionsupporting
confidence: 91%
“…The overall 2-, 5-, and 10-year survival rates were similar after these two treatments. Previous studies on the treatment of HNCUP came to different conclusions: some studies found a statistically increased survival rate for treatment including ND [4, 8, 29]. In one study, the indication for ND was questioned since no significant difference in survival was found between the groups [14], and in other studies no statistically significant differences in survival between the treatment groups were reported, and no conclusions about the optimal treatment were drawn [2, 6, 13, 22, 3032].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Christiansen et al observed significantly higher 5-year survival and neck control rates (55.6% vs. 18.2% and 90.9% vs. 40.9%, respectively) for patients treated with neck dissection and adjuvant RT compared with biopsy plus RT (20) . Wallace et al similarly noted superior neck control and cause-specific survival in HNCUP patients undergoing neck dissection in addition to RT (21) .…”
Section: Discussionmentioning
confidence: 99%